Marketing Analysis Of Beef Cattle In Landono And Mowila Subdistricts Of South Konawe Regency - Munadi, Laode; Rahim Aka; La Ode Muh Munadi; Razak Ali; Muhammad Amrullah Pagala; Syamsuddin (International Journal of Science, Technology & Management, 2021)
Research has been conducted in Landono and Mowila Subdistricts of South Konawe Regency in October-December 2020. The subjects of the study were ranchers and beef cattle traders. Location determination is done intentionally (purposive sampling) while farmers who become respondents are taken as many as 60 people, consisting of 30 respondents each sub-district, which is determined randomly simple (simple random sampling). Research variables are characteristics of respondents including age, education, business experience, number of family members, channels and marketing institutions, margins, costs and profits between marketing agencies. The results showed marketing channels, namely, Farmers?The Final Consumer (Channel I), Farmers ? End Consumer ? Collectors (Channel II), Farmers ? Large Traders? End Consumers (Channel III), Farmers? Collector Traders? Large Traders?The Final Consumer (Channel IV). Marketing margin on channel III (Rp 1,088,571/tail) and channel IV (Rp 1,088,571/tail), lowest on channel II (Rp 765,556/tail). The institutions that get the highest profit are large traders (Rp 998,571/tail), the lowest collector traders (Rp 575,556/tail).